(3cJGH GdfhGOQs - (3SYjO Hf GhS Hf KGHJ Hf RjO Hf bjS GdCfUGQj, CHh RjO,J (B215 (3g` s
(3ChdgG (B:s
(3jHJOF HaUd ai Gdfbd ai GdPgH hGdaVI hGdYQhV s
(3BNQgG (B:s
(3jfJgi HCKfGA eG LGA ai MjGRI GdOghf s
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B220s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG CQVg s
Keywords: (3GddZIs